Antifungal ef fect of Streptomyces sp. RL8 strain and its promoting action on the germination and initial growth of Tépari beans (Phaseolus acutifolius Gray) (TERRA LATINOAMERICANA, 2022)
The Streptomyces sp. RL8 strain was characterized based on its antagonistic activity against phytopathogenic fungi, solubilization of phosphates, production of siderophores, and its ef fect on the germination and initial in vitro growth of Tépari beans (Phaseolus acutifolius Gray), under controlled conditions. A completely randomized experimental design was applied with a bacterial treatment based on RL8 (T) and distilled water as Control treatment (C), with four replicates per treatment and 10 seeds per replicate. The response variables studied were the percentage and germination rate (GP and GR), stem and root length (ST and RL), fresh and dry biomass of aerial part (FBAP and DBAP) and fresh and dry biomass of root (FRB and DRB). RL8 showed antagonistic activity against four phytopathogens of the f ive evaluated, promoted the production of siderophores and the solubilization of phosphates. On an experimental scale, signif icant dif ferences were observed with respect to the control group in GP (65.83 vs 30%), GR (4.16 vs 2.25), SL (3.81 vs 1.65 cm) and RL (5.61 vs 2.13 cm), FBAP (2736.75 vs 18.46. 75 mg), DBAP (608.75 vs 361.5 mg), FRB (347.0 vs 115.75 mg) and DRB (101.25 vs 58.25 mg). These results conf irm a positive ef fect of RL8 on the germination and initial growth of Phaseolus acutifolius Gray, revealing its potential to be used in its organic or traditional cultivation. Its application on a pilot scale and its evaluation as an alternative for agroecological production in greenhouse and in the f ield is suggested.
Keywords: actinomycetes; phytopathogens; phosphate solubilization; siderophores; biomass production